2016
DOI: 10.4054/demres.2016.35.34
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of rural out-migration in Ethiopia: Who stays and who goes?

Abstract: Lack of knowledge on migration in rural Ethiopia 2 Challenges of migration studies 3 Conceptual framework and exploratory analysis 4 Methodology 4.1 Study sites and sampling 4.2 Method of data collection 4.3 Methods of data analysis 5 Characteristics of the sampled households and migrants 5.1 Comparison of the sample with rural Ethiopia and the Amhara region 5.2 Characteristics of the migrants 6 Determinants of migration decisions 6.1 Binary logistic regression explaining the propensity to migrate 6.2 Determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
5
32
0
Order By: Relevance
“…In general, those moving to or leaving urban areas tend to be more highly educated than rural‐rural migrants and non‐migrants (Table ; Figure ). Other studies in Ethiopia have found that internal migrants tend to be more highly educated than non‐migrants (Tegegne and Penker ; Bezu and Holden ), and Blunch and Laderchi () found that migrants obtain higher returns to their education than non‐migrants. These authors note that in, addition to economic opportunity, educational facilities in urban areas can be an attractive factor.…”
Section: The Ethiopian Contextmentioning
confidence: 95%
“…In general, those moving to or leaving urban areas tend to be more highly educated than rural‐rural migrants and non‐migrants (Table ; Figure ). Other studies in Ethiopia have found that internal migrants tend to be more highly educated than non‐migrants (Tegegne and Penker ; Bezu and Holden ), and Blunch and Laderchi () found that migrants obtain higher returns to their education than non‐migrants. These authors note that in, addition to economic opportunity, educational facilities in urban areas can be an attractive factor.…”
Section: The Ethiopian Contextmentioning
confidence: 95%
“…The most susceptible areas to water scarcity and management of this problem are those in arid and semiarid zones. Some results of empirical studies focused on migration in droughtaffected areas have already been published (Findley, 1994;Morrissey, 2013;Rain, 2000;Tegegne & Penker, 2016;Vidyattama, Cassells, Li, & Abello, 2016). Although there is a significant number of these studies (CLIMIG, 2018), there is still a need for a deeper understanding of the ongoing processes that push people to migration.…”
Section: Introductionmentioning
confidence: 99%
“…This result contrasts with the hypothesis that the size of the family and more importantly household's experience of shocks drive them to send out a member. In their study on Ethiopia, Tegegne and Penker (2016) found household's size to be a significant predictor of rural out−migration. This difference in results may be explained by the local context, and more likely by the fact that a single year was used here for the regression analysis with inherent endogeneity issues.…”
Section: Reasons For Migration At Household Level: Both Wealth and Rementioning
confidence: 97%
“…Due to data and time limitations, the statistical analyses developed in the paper only represent a preliminary stage with successive descriptive and inferential statistics for which all tests adopt the 1 percent and 5 percent significance levels. The main caveat related to the results is the endogeneity of migration variables (discussed further in sections 2.1 and 4.1): because the analyses rely on a single wave (year) of surveys, they do not allow to capture the direction of causality between migration and the selected variables (Tegegne and Penker, 2016). A comparative bivariate descriptive analysis for rural and urban migrant households, as well as for rural migrant households (MHHs) and non−migrant households (NMHHs), was first developed in order to provide key socio−demographic information on rural out−migrants' profiles.…”
Section: Statistical Analyses Based On the Rural Livelihood Informmentioning
confidence: 99%
See 1 more Smart Citation